2007
DOI: 10.2989/17280580709486645
|View full text |Cite
|
Sign up to set email alerts
|

Youth violence: A review of risk factors, causal pathways and effective intervention

Abstract: This paper presents a review of theoretical and empirical research on risk factors for: 1) the development of violent and other antisocial behaviour; 2) international interventions targeting antisocial, including violent youths; and 3) outcome evaluations and meta-analyses of interventions targeting antisocial, including violent youths. Taken together, the international literature indicates that interventions which effectively reduce violent and other antisocial behaviours are informed by a number of generic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 0 publications
0
17
0
2
Order By: Relevance
“…Further, several studies have found a relationship between social disorder (e.g., indicated by levels of concentrated poverty, residential instability, and ethnic diversity; signs of physical disorder; or level of social cohesion and control among neighbors) and adolescent delinquency and deviant behavior (Chung & Steinberg, 2006; Sampson, Raudenbush, & Earls, 1997; van der Merwe & Dawes, 2007), both of which are risk factors for sexual violence (Tharp et al, 2013). Thus, the relationship between alcohol and sexual violence perpetration might be mediated by neighborhood factors, such as disorganization.…”
Section: Relationship Between Alcohol and Sexual Violence Perpetrationmentioning
confidence: 99%
“…Further, several studies have found a relationship between social disorder (e.g., indicated by levels of concentrated poverty, residential instability, and ethnic diversity; signs of physical disorder; or level of social cohesion and control among neighbors) and adolescent delinquency and deviant behavior (Chung & Steinberg, 2006; Sampson, Raudenbush, & Earls, 1997; van der Merwe & Dawes, 2007), both of which are risk factors for sexual violence (Tharp et al, 2013). Thus, the relationship between alcohol and sexual violence perpetration might be mediated by neighborhood factors, such as disorganization.…”
Section: Relationship Between Alcohol and Sexual Violence Perpetrationmentioning
confidence: 99%
“…In contexts heavily affected by HIV/AIDS and poverty, improved understanding of the influence of age, gender and other possible mediating factors on child psychosocial well-being will help us better design interventions to support the precise physical and mental health needs of children as they mature. Life skills programs have been found to be effective for improving interpersonal skills and reducing antisocial behavior in youth (Breinbauer & others, 2005; Patel, Flisher, Nikapota, & Malhotra, 2008; van der Merwe & Dawes, 2007), and more recently, family strengthening programs have demonstrated some promise in improving communication and monitoring and control by parents and caregivers (Bell et al, 2008; Paruk, Petersen, & Bhana, 2009). Interventions to improve psychosocial well-being in the context of poverty and HIV/AIDS, however, must also address food security and general economic and social conditions.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of social disorganization in communities often result in an absence of effective social controls to constrain and discourage antisocial behavior (Chung & Steinberg, 2006;Sampson, Raudenbush, & Earls, 1997). Indeed, indicators of social disorganization such as neighborhood disorder, weak social ties, and low levels of informal social controls (the extent to which community adults cooperate to regulate the behavior of neighborhood youths) and collective efficacy have been consistently linked to adolescent delinquency and deviant behavior (Leventhal & Brooks-Gunn, 2000;van der Merwe & Dawes, 2007). Social disorder and social controls might also impact aggressive behavior within more defined and structured communities, such as schools.…”
Section: Social Disorganization/lack Of Social Controlsmentioning
confidence: 99%
“…The availability of drugs and alcohol in a community has been associated with community violence rates, as well as rates of violent delinquency (e.g., van der Merwe & Dawes, 2007). Both the density of alcohol outlets and the density of drug crimes per capita can predict violent crime rates in those communities (Gorman, Zhu, & Horel, 2005).…”
Section: Availability Of Drugs/alcohol In Communitymentioning
confidence: 99%